The Role of Financial Risk Management in Promoting Sustainable Development: An applied study on Saudi sports clubs 2025 - Elhag, Noureldaim Eltayeb Yousif (Journal of Risk and Crisis Management, 2025)
The study aimed to clarify the role of financial risk management in promoting sustainable development in Saudi sports clubs.The scientific significance of this study lies in its attempt to enrich the Arabic library by contributing scientifically to the understanding of the role of financial risk management in promoting sustainable development. Its importance is further highlighted by the potential benefits of the study's results in applying financial risk management methods to contribute to enhancing sustainable development.The study utilized an analytical descriptive methodology, employing a stratified sample of 210 individuals from the research community. The study reached several key findings, the most important of which are: there is a role for financial risk management in enhancing the sustainable development of clubs, and Saudi sports clubs utilize artificial intelligence for financial risk management. A positive correlation (0.83) at the 0.01 level was found between financial risk management and the enhancement of sustainable development in Saudi sports clubs. The application of financial risk management frameworks, such as COSO and ISO 31000, aids in promoting sustainable development in Saudi sports clubs.The study recommends that  Saudi sports clubs implement principles of governance, financial disclosure, and transparency regarding risks to enhance trust among investors and stakeholders. Furthermore, it emphasizes the importance of training financial and administrative staff in the areas of financial risk management and sustainable development to ensure effective strategy implementation.
Keywords: Financial Risk Management; Governance; Sustainable Development; COSO Framework; ISO 31000